Aktivitas Antiradikal DPPH (2,2 difenil-1-pikrilhidrazill) Kombinasi Seduhan Daun Kayu Jawa (Lannea coromandelica (Houtt.) Merr.) dan Daun Salam (Syzygium polianthum Wight) - Kismawati; Nasrudin; Rahmanpiu (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2022)
Research on the Antiradical Activity of DPPH (2,2-diphenyl-1-picrylhydrazil) Combination of Javanese Wood Leaf (Lannea coromandelica Hout Merr) and Salam Leaf (Syzygium polianthum Wight) infusion has been carried out. This study aims to determine the comparison of the combination of steeping DKJ and DS powder which shows antioxidant activity close to 50% and to determine the optimal concentration of the combination of steeping DKJ and DS in counteracting DPPH radicals. The antioxidant activity test was carried out using the DPPH method. The combination of DKJ and DS steeping powders that showed antioxidant activity close to 50% was in the ratios A3, A4, A5, A6, B2, B3, B4, B5, B6, C1, C2, C3, C4, C5, C6, D1, D2, D3, D4, D5, D6, E1, E2, E3, E4, E5, E6, F1, F2, F3, F4, F5 and F6 from 36 combinations.